2018
DOI: 10.7150/ijbs.26932
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Roles of Translation Initiation Factor 3b

Abstract: Translation has important roles in almost all physiological and pathological processes, and translation initiation factors are particularly relevant to the translation initiation step, which is the most important step in translation regulation. Translation initiation factor 3b (eIF3b), a key subunit of the largest translation initiation factor 3 (eIF3), is widely considered a scaffold protein that acts to ensure the accuracy of translation initiation. A series of recent finds has revealed that eIF3 is closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Thus, mutations of ubiquitin C ( UBC ) may be associated with resistance to anti-PD-1 therapy in melanoma. Fourth, some studies have revealed that translation initiation factor 3b (eIF3b), a key subunit of the largest translation initiation factor that acts to ensure the accuracy of translation initiation, is closely related to oncogenesis 56 . Xu et al 57 reported that EIF3B gene expression can accelerate the progression of esophageal squamous cell carcinoma by activating β-catenin signaling, which can promote immune escape and resistance to anti-PD-1 therapy 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, mutations of ubiquitin C ( UBC ) may be associated with resistance to anti-PD-1 therapy in melanoma. Fourth, some studies have revealed that translation initiation factor 3b (eIF3b), a key subunit of the largest translation initiation factor that acts to ensure the accuracy of translation initiation, is closely related to oncogenesis 56 . Xu et al 57 reported that EIF3B gene expression can accelerate the progression of esophageal squamous cell carcinoma by activating β-catenin signaling, which can promote immune escape and resistance to anti-PD-1 therapy 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, copy-number alterations of ubiquitin C ( UBC ) may be associated with resistance to anti-PD-1 therapy in melanoma. Fourth, some studies have revealed that translation initiation factor 3b ( EIF3B ), a key subunit of the largest translation initiation factor that acts to ensure the accuracy of translation initiation, is closely related to oncogenesis [68]. Xu et al [69] reported that EIF3B can accelerate the progression of esophageal squamous cell carcinoma by activating β-catenin signaling, which can promote immune escape and resistance to anti-PD-1 therapy [4].…”
Section: Resultsmentioning
confidence: 99%
“…The following are possible explanations: (i) EIF3B might enhance the proliferation and migration and inhibit the apoptosis of immature WBC by interfering with cell cycle progression in the bone marrow, which resulted in the overproduction of abnormal WBCs and bone marrow blasts, therefore, higher EIF3B expression was associated with elevated WBC level and bone marrow blasts in adult Ph − ALL patients. 7 , 14 (ii) EIF3B might maintain malignant cell survival via promoting cell proliferation enhancement factor such as C3G (inhibited proapoptotic pathway such as the p38 mitogen activated kinase-like protein [MAPK] pathway and the extracellular regulated MAP kinase/proteinkinase B [ERK/AKT] cascade), which led to exacerbated clinical features in adult Ph − ALL patients. 15 However, the inferential explanations needed further validation.…”
Section: Discussionmentioning
confidence: 99%
“…Eukaryotic translation initiation factor 3 (EIF3), the most complex translation initiation factor consisting of 13 non-identical subunits (EIF3A to M), is vital in the entire process of translational initiation processes. 7 As a major scaffold protein, EIF3 subunit B (EIF3B) contains two domains (the N-terminal domain and the WD40β domain), which is related to multiple cellular processes, including cell cycle progression, apoptosis, transcription, signal transduction and others. 7 A series of recent findings has unraveled that EIF3B participates in the pathogenesis of multiple cancers including hematological malignancies.…”
Section: Introductionmentioning
confidence: 99%